Predictive Lending AI - Kommaraju Rupa Kusuma, Manne Suneetha (Mathematical Statistician and Engineering Applications, 2023)
The product Predictive Lending AI is a AI based Automatic Lending Solutionfor Non-Banking Financial Company (NBFC). It helps a global lending firm to reduce theloan processing time by 40%, minimize business risk and increase revenues with effectiveup-sellingoflendingproducts.Therearethreeuse cases(Applicationscoring,Defaulter Prediction and?Churn Prediction).?The first use case is Application Scoring inwhich we calculate a score based on the input and approve a loan based on that score. Thesecond use case is about Loan Defaulter Prediction. The person who takes loan from anorganization and doesn’t repay the loan amount is called Loan defaulter. The third usecase is about Churn Prediction. Churn is defined as the movement of customers from oneprovidertoanother.